Cultural Norms And Social Behavior Of The Mattampawalie Village Community - Aulia, Nur; Kamaruddin, Syamsu A; Awaru, A. Octamaya Tenri (Jurnal Ilmiah Mandala Education (JIME), 2025)
This research uses a long process, starting with a literature review, then interviews with a qualitative approach is one of the most effective ways to understand a particular phenomenon in depth about the cultural norms and social behavior of the Mattampawalie Village community. The results of this study show that; 1) Cultural norms in Mattampawalie Village play a role as a guideline for life that shapes the mindset and social behavior of the community; 2) Values such asshame and pace, mutual cooperation, and respect for traditional figures are still highly respected in daily life; 3) The social behavior of the community shows a strong attachment to customs, such as in conflict resolution, etiquette, and participation in social activities.; 4) The community is able to adapt to social and technological changes without abandoning core cultural values.; 5) Cultural norms persist and become the basis of social cohesion and collective identity of the community amidst the flow of modernization. Understanding cultural norms is important to see how local values still influence the social behavior of the community amidst changing times. This research contributes to the preservation of local cultural values, as well as being a reference in strengthening character education and social policies based on local wisdom.